Autonomous Learning Strategies for Academic Speaking by English Education Department Students - Ahmad Wael; Muhaiminah Akib; Hasanudin Hasanudin; Rizal Akib (J-SHMIC : Journal of English for Academic, 2023)
Autonomous is the individual capacity to take responsibility for their own learning activities. Autonomous learning adapted learning method that learners use to obtain their own learning needs and goals, determine the most current learning method, and assess learning activity. This research aims at identifying students’ autonomous learning strategies in academic speaking class. There were 20 students from the English Education Department were involved to gather the data. This study employed a quantitative approach in order to get the data. The data were taken by using a questionnaire. The result shows that the general description of the students of the English Education Department at Universitas Muhammadiyah Sorong was not included a specific description of how the students employed the autonomous learning strategy for learning particularly in academic speaking. The researcher found two kinds of autonomous learning strategies which were metacognitive strategy and social mediation strategy.